Teachers’ Competence in Teaching English to Young Learners Using Syntactic Approach in Kota Lhokseumawe - nurlaila nurlaila (ELITE JOURNAL, 2019)
Teaching English at primary school is difference from teaching English at junior or senior high school because the teacher must really pay attention on the students characteristics. The English teacher must have English background and have ever had training on ways of teaching EYL. This TEYL (Teaching English for Young Learners) program is necessary to be well prepared. Qualified and competent teachers are necessary to be prepared for the implementation of this curriculum. In delivering the materials, they must have competences or abilities in mastering the materials especially on the use of good English pattern to make the young learners familiar with the language. This research is aimed at investigating the EYL teacher competence namely pedagogic and professional competences using syntactic approach especially at the high level class students of primary school in Kota Lhokseumawe. The method used in this research is called descriptive survey research. According to Ary Donald descriptive survey research is divided into some classification based on their focus and scope (census and sample surveys) or according to the time frame for data collection (longitudinal and cross-sectional surveys). The population of the research were all primary schools in Kota Lhokseumawe, while the sample were only fourteen schools who still applied English as the subject or local content. The result of the research shown that pedagogic and professional competences of EYL teachers in teaching English using syntactic approach shown us that from 14 respondents is 100%, or all of respondents obtained the result of very good. It means that most of EYL teacher in Kota Lhokseumawe who implemented English as local content had fulfilled the criteria of very good.